FUNDING SOURCE DIVERSIFICATION STRATEGIES IN NON-FORMAL EDUCATION: A Field Study at PKBM Al-Islam Giwangan Yogyakarta - Aulia, Nur Annisa; Shaleh (Wahana Islamika Jurnal Studi Keislaman, 2025)
Financing management in non-formal education requires an effective strategy for diversifying sources of funds in order to ensure operational sustainability and improve the quality of educational services. As a non-formal education institution, PKBM Al-Islam Giwangan Yogyakarta faces challenges in maintaining funding stability, so an innovative approach is needed in obtaining and managing various sources of funds. This study aims to identify the funding source diversification strategy implemented by PKBM Al-Islam Giwangan Yogyakarta and the factors that contribute to its success. The method used in this research is a qualitative approach with field studies through in-depth interviews, observation, and document analysis. The results show that diversification of funding sources is done through a combination of funding from the government, community donations, student contributions, cooperation with private institutions, and utilization of community-based productive businesses. The success of this strategy is determined by visionary leadership, transparent and accountable financial management, and active participation from all stakeholders. In addition, the use of technology in the financial system also plays a role in improving the efficiency and transparency of fund management. By implementing the right diversification strategy, PKBM Al-Islam Giwangan Yogyakarta can reduce dependence on one source of funding and increase financial stability, thus supporting the sustainability of non-formal education for the community.